The long- and short-term variability of breathing induced tumor motion in lung and liver over the course of a radiotherapy treatment. Issue 2 (February 2018) - Dhont, Jennifer; Vandemeulebroucke, Jef; Burghelea, Manuela; Poels, Kenneth; Depuydt, Tom; Van Den Begin, Robbe; Jaudet, Cyril; Collen, Christine; Engels, Benedikt; Reynders, Truus; Boussaer, Marlies; Gevaert, Thierry; et al.
Abstract: Purpose: To evaluate the short and long-term variability of breathing induced tumor motion. Materials and methods: 3D tumor motion of 19 lung and 18 liver lesions captured over the course of an SBRT treatment were evaluated and compared to the motion on 4D-CT. An implanted fiducial could be used for unambiguous motion information. Fast orthogonal fluoroscopy (FF) sequences, included in the treatment workflow, were used to evaluate motion during treatment. Several motion parameters were compared between different FF sequences from the same fraction to evaluate the intrafraction variability. To assess interfraction variability, amplitude and hysteresis were compared between fractions and with the 3D tumor motion registered by 4D-CT. Population based margins, necessary on top of the ITV to capture all motion variability, were calculated based on the motion captured during treatment. Results: Baseline drift in the cranio-caudal (CC) or anterior-poster (AP) direction is significant (ie. >5 mm) for a large group of patients, in contrary to intrafraction amplitude and hysteresis variability. However, a correlation between intrafraction amplitude variability and mean motion amplitude was found (Pearson's correlation coefficient, r  = 0.72, p  < 10 −4 ). Interfraction variability in amplitude is significant for 46% of all lesions. As such, 4D-CT accurately captures the motion during treatment for some fractions but not for all. Accounting for motion variability during treatment increases the PTV margins in all directions, most significantly in CC from 5 mm to 13.7 mm for lung and 8.0 mm for liver. Conclusion: Both short-term and day-to-day tumor motion variability can be significant, especially for lesions moving with amplitudes above 7 mm. Abandoning passive motion management strategies in favor of more active ones is advised.